2010
DOI: 10.1002/jsfa.4096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flavonol glycoside in mulberry (Morus alba L.) leaf on glucose metabolism and oxidative stress in liver in diet‐induced obese mice

Abstract: Dietary consumption of Q3MG, the quantitatively major flavonol glycoside in mulberry leaves, improved hyperglycemia in obese mice and reduced oxidative stress in the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 27 publications
3
60
0
2
Order By: Relevance
“…For instance, chlorogenic acid is known to be a strong antioxidant and it is also known to reduce plasma glucose in humans (Iwai et al 2012). Similarly, quercetin-3-6-malonylglucoside has been reported to be highly bioactive and known to be effective against oxidation of low-density lipoprotein and oxidative stress in the liver (Katsube et al 2010). Extracts of black currant leaves have been demonstrated to possess anti-inflammatory and anti-virus activities (Tabart et al 2011;Ehrhardt et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, chlorogenic acid is known to be a strong antioxidant and it is also known to reduce plasma glucose in humans (Iwai et al 2012). Similarly, quercetin-3-6-malonylglucoside has been reported to be highly bioactive and known to be effective against oxidation of low-density lipoprotein and oxidative stress in the liver (Katsube et al 2010). Extracts of black currant leaves have been demonstrated to possess anti-inflammatory and anti-virus activities (Tabart et al 2011;Ehrhardt et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that quercetin 3-(6-malonyglucoside) is the major flavonol glycoside in mulberry leaves, and that it has a strong antioxidant effect (Katsube et al, 2006). We also reported that it altered blood glucose levels via a mechanism different from that of 1-deoxynojirimycin (DNJ) (Katsube et al, 2010). Our research group reported that chlorogenic acid, an abundant polyphenol in mulberry leaves, plays an important role in the antioxidant activity of leaf extracts (Katsube et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Dong-eui-bo-gam, the oldest Korean medicinal book, Morus alba leaf (MAL), also known as Mori folium when used as a herbal medicine, alleviates the symptoms of beriberi, body swelling, dropsy and diabetes (1). Modern medical studies of the leaves of the white mulberry have reported anti-atherogenic (2), anti-hypertensive (3,4), anti-obesity (5), anti-diabetic (6) and liver protective (7,8) effects.…”
Section: Introductionmentioning
confidence: 99%